Tantangan Teologi Postmodern Terhadap Sola Scriptura - Kakisina, Memoryni (Sekolah Tinggi Teologi Injili Indonesia Palu, 2026)
This paper examines the challenges posed by postmodern theology to the principle of Sola Scriptura within a Reformed theological framework. Employing a qualitative literature-based approach, the study analyzes the development of postmodern epistemology and its implications for truth, authority, and biblical interpretation. The findings indicate that relativism, deconstruction, and the rejection of metanarratives constitute major challenges to Sola Scriptura, particularly regarding the authority of Scripture as absolute, final, and infallible truth. The shift from a theocentric to an anthropocentric orientation further reinforces subjective approaches to Christian faith. This paper therefore reaffirms the importance of Sola Scriptura as a theological foundation that safeguards the integrity of divine revelation in a postmodern context.